A Case of Hypocalcemia with Severe Vitamin D Deficiency following Treatment for Graves’ Disease with Methimazole - Kazuyuki Miyashita; Tetsuyuki Yasuda; Hideaki Kaneto; Akio Kuroda; Tetsuhiro Kitamura; Michio Otsuki; Yasuyuki Okamoto; Noboru Hamada; Munehide Matsuhisa; Iichiro Shimomura (Case Reports in Endocrinology)
We herein report the case of a 41-year-old Japanese female office worker who developed symptomatic hypocalcemia with severe vitamin D deficiency following treatment for Graves’ disease with methimazole. The patient’s hypocalcemia was mainly caused by vitamin D deficiency due to unbalanced diets and inadequate exposure to sunlight in addition to the resolution of hyperthyroidism. Vitamin D deficiency is increasing worldwide, and it has been more recently shown to relate to the pathogenesis of Graves’ disease. However, vitamin D deficiency as a cause of hypocalcemia has received little attention. Taken together, this case suggests that we should take more care in calcium kinetics and vitamin D status during treatment for Graves’ disease with antithyroid drugs.